2016
DOI: 10.1017/gheg.2016.7
|View full text |Cite
|
Sign up to set email alerts
|

An Australian model of the First 1000 Days: an Indigenous-led process to turn an international initiative into an early-life strategy benefiting indigenous families

Abstract: Internationally, the 1000 days movement calls for action and investment in improving nutrition for the period from a child's conception to their second birthday, thereby providing an organising framework for early-life interventions. To ensure Australian Indigenous families benefit from this 1000 days framework, an Indigenous-led year-long engagement process was undertaken linking early-life researchers, research institutions, policy-makers, professional associations and human rights activists with Australian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…The results of review show that only two studies addressed international CI initiatives. These CI initiatives utilized two international programs; the Alive & Thrive (Michaud-Létourneau et al 2019) and the 1000 days movement (Ritte et al 2016).…”
Section: International Partnerships and Their Their Backbone Structurmentioning
confidence: 99%
“…The results of review show that only two studies addressed international CI initiatives. These CI initiatives utilized two international programs; the Alive & Thrive (Michaud-Létourneau et al 2019) and the 1000 days movement (Ritte et al 2016).…”
Section: International Partnerships and Their Their Backbone Structurmentioning
confidence: 99%
“…Recent Australian data indicate that 46% of Aboriginal birthing mothers live in the lowest socioeconomic areas, 52% are aged below 24 years and are 8 times as likely as non-Aboriginal mothers to be teenagers [54]. To enact the NCF and 1000 Days Australia [61,62] these families require targeted interventions that are experienced as culturally safe and continue after the neonatal period. This review identified that continuity of care in the provision of maternity services appeared to have a positive impact on maternal and infant health outcomes, including improvements in antenatal attendance, better monitoring and management of risk factors, lower rates of preterm birth, higher infant birth weight, and lower perinatal morbidity and mortality, and was the preferred approach for Aboriginal families.…”
Section: Discussionmentioning
confidence: 99%
“…[69] Arabena talks about a First Nations model aimed at strengthening all families so they can give their children the best start in life [52,61]. Although Elders, community members and early childhood program developers work to provide coordinated, comprehensive, culturally informed interventions to support families [62], looking at health care holistically we need to examine the health care systems and workforce structureat present even though we know best practice from research, health care systems, structure and workforce are not providing optimum health care outcomes without a focus on continuity of care beyond the perinatal period.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, findings from internal comparisons, i.e. the PR calculated in the present study, are intended to be generalisable beyond the study population (84,85) .…”
Section: Limitationsmentioning
confidence: 96%